A phenomenological exploration of work-related post-traumatic growth among high-functioning adults maltreated as children - Kaye-Tzadok, Avital; Icekson, Tamar (Frontiers in Psychology, 2022)
Childhood maltreatment is a highly prevalent traumatic experience, and its adverse psychological and behavioral consequences are well-documented. Notwithstanding these adverse outcomes, many individuals who suffered from traumatic experiences report posttraumatic growth, i.e., transformative positive changes resulting from their struggle to cope. Posttraumatic growth has been extensively explored among adult survivors of childhood maltreatment, with findings indicating both the traditional (personal strength, relating to others, appreciation of life, openness to new possibilities, and spiritual change) as well as abuse-specific domains of growth (e.g., increased ability to protect themselves from abuse). However, little attention has been given to vocational aspects of posttraumatic growth among survivors, despite the central role and importance of work in adulthood. Exploration of posttraumatic growth at work has focused on certain vocational traumatic experiences, such as those which occur in the military, or through secondary trauma. This exploratory qualitative study focuses on the question: What is the lived experience of work-related post traumatic growth among high-functioning adult survivors of CM? Twenty in-depth interviews were held with high-functioning working adults who were maltreated as children. Phenomenological analysis was applied to the retrospective data reported in these interviews. Rich descriptions of work-related positive psychological changes were provided by all participants. Analysis revealed that survivors' posttraumatic growth corresponded with all five "traditional" domains of growth: changes in self, relating to others, new possibilities, finding meaning to the abuse, and appreciation of life. It also revealed that work is perceived as a form of resistance (a subtheme of changes in self), and that finding meaning entails three emerging subthemes: being a survivor and a role model, giving others what was needed and never received, and making a better world. While the vocational lives of survivors of childhood maltreatment have rarely been examined through the lens of posttraumatic growth, our results show this lens to be highly valuable. Work related posttraumatic growth has relevance not only regarding vocational traumas occurring in adulthood as has been previously studied, but also in the context of childhood traumas. Moreover, our research broadens the understanding of the possible domains of work-related growth.